Earthquake behavior of M1 minaret of historical Sultan Ahmed Mosque (Blue Mosque) - Kocaturk, Turgut; Erdosgan, Yildirim Serhat (TECHNO-PRESS, 2016)
Minarets are almost the inevitable part of Mosques in Islam and according to some, from a philosophical point of view, today they symbolize the spiritual elevation of man towards God. Due to slenderness, minarets are susceptible to earthquakes and wind loads. They are mostly built in a masonry style by using cut limestone blocks or occasionally by using bricks. In this study, one minaret (M1 Minaret) of one of the charmest mosques of Turkey, Sultan Ahmed Mosque, popularly known as Blue Mosque, built between 1609 and 1616 on the order of Sultan Ahmed by the architect Mehmet Agha is investigated under some registered earthquake loads. According to historical records, a great earthquake hit Istanbul and/or its close proximity approximately every 250 years. Ottomans tackled with the problem of building earthquake resistant, slender minarets by starting to use forged iron connectors with lead as a filler to fix them to the upper and lower and to adjacent stones instead of using traditional mortar only. Thus, the discrete stones are able to transfer tensile forces in some sense. This study investigates the contribution of lead to the energy absorption capacity of the minaret under extensive earthquakes occurred in the region. By using the software ANSYS/LS-DYNA in modelling and investigating the minaret nonlinearly, it is found out that under very big recorded earthquakes, the connectors of vertical cast iron-lead mechanism play very important role and help to keep the structure safe.
Keywords: historical masonry structures; finite element analysis; discrete element method; earthquake analysis; earthquake resistant structures; SEISMIC RESPONSE; ELEMENT MODEL; MASONRY; Engineering